Vulnerability Assessment and Obstacle Degree Analysis of Marine Economic System in Shandong Province Based on Entropy Weight TOPSIS Model - Zhen LI (Haiyang Kaifa yu guanli, 2023)
In the context of constructing a powerful marine country, the research on the vulnerability of the marine economic system in Shandong Province is of great significance for the sustainable development of the marine economy. This paper constructed an index system of marine economic system vulnerability from four aspects: coping capability, sensitivity, coercion and elasticity, and calculated the index weight based on the entropy weight method. The vulnerability of the system was analyzed, and combined with the obstacle degree model, the first five obstacles affecting the vulnerability of the marine economic system were studied in detail from the index level. The study found: First, the vulnerability of the marine economic system in Shandong Province experienced obvious fluctuations from 2007 to 2014, and since 2014, the degree of system vulnerability of the marine economy in Shandong Province has shown a downward trend; overall, the sensitivity showing a gradual upward trend, the coping ability and coercion have experienced the initial big ups and downs, and have shown upward momentum since 2009 and 2013, respectively. Except for the extremely high value in 2013, the other years showed relatively stable elasticity. Finally, through the analysis of the obstacle degree of the standard layer in each year, it was found that the coping ability (R) and sensitivity (S) played a major role, and through the obstacle degree analysis of the index layer, it was found that the total industrial wastewater discharge (10, 000 tons) ), foreign exchange income from inbound tourism (10, 000 US dollars), investment in fixed assets of the whole society (100 million yuan), passenger throughput (10, 000 person-times), marine industrial structure diversification index, per capita urban road area (square meters), marine tertiary industry accounted for ratio (%) and number of protected areas (pieces) was the main obstacle.